2003
DOI: 10.1523/jneurosci.23-12-05123.2003
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Regulates Interneuron Migration in the Developing Neocortex

Abstract: The chemotactic factors directing interneuron migration during cerebrocortical development are essentially unknown. Here we identify the CXC chemokine receptor 4 (CXCR4) in interneuron precursors migrating from the basal forebrain to the neocortex and demonstrate that stromal cell-derived factor-1 (SDF-1) is a potent chemoattractant for isolated striatal precursors. In addition, we show that CXCR4 is present in early generated Cajal-Retzius cells of the cortical marginal zone. In mice with a null mutation in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
432
3
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(467 citation statements)
references
References 39 publications
27
432
3
4
Order By: Relevance
“…More recently further developmental phenotypes have been observed in CXCR4 null mice. In the CNS, it was found that the migration of interneuron progenitors from the ganglionic eminence to the cerebral cortex was somewhat compromised (Stumm et al, 2003). Interestingly, phenotypes have also been observed in the peripheral nervous system, whereby it was observed that neural progenitors that migrated from the dorsal neural tube expressed CXCR4.…”
Section: Chemokines and Developmentmentioning
confidence: 97%
“…More recently further developmental phenotypes have been observed in CXCR4 null mice. In the CNS, it was found that the migration of interneuron progenitors from the ganglionic eminence to the cerebral cortex was somewhat compromised (Stumm et al, 2003). Interestingly, phenotypes have also been observed in the peripheral nervous system, whereby it was observed that neural progenitors that migrated from the dorsal neural tube expressed CXCR4.…”
Section: Chemokines and Developmentmentioning
confidence: 97%
“…Various cytokines and growth factors, such as platelet derived growth factor [258,259], fibroblast growth factor 2 [260], class 3 semaphorins [261,262], Sonic hedgehog [263], stem cell factor [264], the chemokine stromal derived factor 1 (CXCL12) [265][266][267][268][269], epidermal growth factor [270], and vascular endothelial growth factor [271] increased the migration of progenitor cells of the oligodendrocyte or neuronal lineages in vitro, and were implicated in CNS development in vivo. Very little is known, however, on the molecular signals that control neural stem and progenitor cell migration in inflammation.…”
Section: Route Of Cell Deliverymentioning
confidence: 99%
“…These include deficits in β-lymphopoiesis and myelopoiesis (Nagasawa, 2007;Nagasawa et al, 1996;Nie et al, 2004;Zou et al, 1998), cardiogenesis (Miao et al, 2007;Nagasawa et al, 1996;Zou et al, 1998), angiogenesis (Tachibana et al, 1998;Zou et al, 1998), neurogenesis (Lu et al, 2002;Stumm et al, 2003;Tran et al, 2007) and germ cell migration and development (Dumstrei et al, 2004). Basically, all of these phenotypes can be explained by the observation that CXCR4 signaling is important in regulating the migration of different types of stem/ progenitor cells.…”
Section: The Chemokine Familymentioning
confidence: 99%
“…The expression patterns for SDF-1 and CXCR4 in the developing DG, as well as the phenotype of CXCR4 knockout mice, are consistent with a model in which SDF-1 is secreted by meningeal cells that line the route of migrating CXCR4 expressing progenitors, and that progenitors are stalled in their migration when CXCR4 signaling is interrupted. Other neuronal phenotypes observed in CXCR4 knockout mice include defects in the placement of developmentally important Cajal-Retzius cells (Berger et al, 2007;Paredes et al, 2006;Stumm et al, 2003), cortical GABAergic interneurons (Stumm et al, 2007;Stumm et al, 2003;Tiveron et al, 2006) and GnRH secreting forebrain neurons (Schwarting et al, 2006). In all of these situations it appears that the progenitors for these neurons utilize SDF-1 mediated chemoattraction to attain their final positions, and that lack of CXCR4 signaling results in interrupted progenitor migration.…”
Section: Development Of the Nervous Systemmentioning
confidence: 99%